2015
DOI: 10.1590/2175-3369.008.001.se03
|View full text |Cite
|
Sign up to set email alerts
|

Rehabitar la Montaña: strategies and processes for sustainable communities in the mountainous periphery of Medellín

Abstract: Thousands of poor, marginal communities' residents die due to landslide events every year. The quick urbanization of mountainous areas, combined with an increased frequency of landslide events induced by heavy rains due to climate change, is leading to increased deaths year after year, and the problem will only get worse. Landscape Architects, trained to analyze and intervene in situations with complex natural and social territorial dynamics, are in position to make positive contributions to mitigating risks i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…We argue that there is also an imbalance in the physical and social elements of included research, with gaps in areas such as governance, warning dissemination, and contingency planning, all of which help translate early warning into early action. An outlier example of pioneering multidisciplinary research focused on high risk areas in Medellin, Colombia (which is a host location for people displaced by conflict), describes the importance of combining social and physical science research and community based approaches to design early warning systems (Claghorn et al 2015). In contexts that experience debilitated systems, networks, and infrastructure with high levels of vulnerability and exposure due to the impact of war, it is crucial to understand the social, political and economic dynamics in the entire value chain of early warning early action.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that there is also an imbalance in the physical and social elements of included research, with gaps in areas such as governance, warning dissemination, and contingency planning, all of which help translate early warning into early action. An outlier example of pioneering multidisciplinary research focused on high risk areas in Medellin, Colombia (which is a host location for people displaced by conflict), describes the importance of combining social and physical science research and community based approaches to design early warning systems (Claghorn et al 2015). In contexts that experience debilitated systems, networks, and infrastructure with high levels of vulnerability and exposure due to the impact of war, it is crucial to understand the social, political and economic dynamics in the entire value chain of early warning early action.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that that population growth in the region has been affected by forced migration, which has caused a constant flow of migrants towards the big cities, as stated in Claghorn et al (2015). These new arrivals normally settle in the hills at the urban periphery, where there is little collection or treatment of wastewater, which therefore tends to be discharged into nearby water bodies, causing a deterioration in water quality that subsequently affects the river.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, strategies to anticipate future growth are focused on long-term collaboration with communities. The research found that a relatively small early investment by the city to prevent the occupation of dangerous sites today would mean significant savings in the future, especially if such coordination is done in close collaboration with existing communities before future growth happens (Claghorn et al 2016).…”
Section: Key Research Insightsmentioning
confidence: 99%